Can platelet indices be used as predictors of complication in subjects with appendicitis? - Ceylan, Bahadır; Aslan, Turan; Çınar, Ahmet; Ruhkar Kurt, Ayşe; Akkoyunlu, Yasemin (Wiener Klinische Wochenschrift, 2016)
Summary Background We examined the changes of mean platelet volume (MPV) and platelet distribution width (PDW) in subjects with appendicitis and whether MPV and PDW could be used to predict the development of c omplication due to appendicitis. Methods The healthy control group, the cases of appendicitis with perforation, and the cases of appendicitis without perforation were compared with regard to MPV and PDW. We determined whether MPV and PDW were independent variables predictive of the development of c omplication in subjects with appendicitis. Results This retrospective case-control study included a total of 362 patients (249 of which were male (68.8 %) and 113 were female (31.2 %); median age, 30 [range, 18–84 years]). One hundred and ninety-two subjects (53 %) presented with appendicitis and 170 (47 %) comprised the healthy control group. Sixty-six (18.2 %) of the subjects with appendicitis developed complication. MPVs were lower in subjects of appendicitis without complication compared to the subjects of appendicitis with complication and the control group (MPV, 9.78 ± 0.99 vs. 10.20 ± 1.21 and 10.14 ± 1.03, respectively [ p = 0.005]). The PDW levels were not different between the three groups. Independent variables predictive of the presence of complication included increased MPV and time from onset of symptoms to hospital presentation (odds ratio[confidence interval], p -value: 1.507[1.064–2.133], 0.021 and 18.887[5.139-69.410], 0.0001, respectively). Conclusions Our findings suggested these, MPV values in cases of appendicitis without complication were lower than the cases with complication and healthy control and MPV is a predictor of the development of complication in subjects with appendicitis.